Plasma Membrane Targeting of Endogenous NKCC2 in COS7 Cells Bypasses Functional Golgi Cisternae and Complex N-Glycosylation - Singh, Richa; Kursan, Shams; Almiahoub, Mohamed Y.; Almutairi, Mohammed M.; Garzón-Muvdi, Tomás; Alvarez-Leefmans, Francisco J.; Di Fulvio, Mauricio (Frontiers in Cell and Developmental Biology, 2017)
Na+K+2Cl– cotransporters (NKCCs) effect the electroneutral movement of Na+-K+ and 2Cl– ions across the plasma membrane of vertebrate cells. There are two known NKCC isoforms, NKCC1 (Slc12a2) and NKCC2 (Slc12a1). NKCC1 is a ubiquitously expressed transporter involved in cell volume regulation, Cl– homeostasis and epithelial salt secretion, whereas NKCC2 is abundantly expressed in kidney epithelial cells of the thick ascending loop of Henle, where it plays key roles in NaCl reabsorption and electrolyte homeostasis. Although NKCC1 and NKCC2 cotransport the same ions with identical stoichiometry, NKCC1 actively cotransports water, whereas NKCC2 does not. There is growing evidence showing that NKCC2 is expressed outside the kidney, but its function in extra-renal tissues remains known. The present study shows molecular and functional evidence of endogenous NKCC2 expression in COS7 cells, a widely used mammalian cell model. Endogenous NKCC2 is primarily found in recycling endosomes, Golgi cisternae, Golgi-derived vesicles and to a lesser extent in the endoplasmic reticulum. Unlike NKCC1, NKCC2 is minimally hybrid/complex N-glycosylated under basal conditions, and yet it is trafficked to the plasma membrane region of hyper-osmotically challenged cells through mechanisms that require minimal complex N-glycosylation or functional Golgi cisternae. Control COS7 cells exposed to hypertonic solutions for 16h were not shrunken, suggesting that both, NKCC1 and NKCC2 may participate in cell volume recovery. However, NKCC2 targeted to the plasma membrane region, or transient over-expression of NKCC2, failed to rescue NKCC1 in COS7 cells where NKCC1 had been silenced. Further, COS7 cells in which NKCC1, but not NKCC2, was silenced exhibited reduced cell size compared to control cells. Altogether, these results suggest that NKCC2 does not participate in cell volume recovery and therefore, NKCC1 and NKCC2 are functionally different Na+K+2Cl– co-transporters.